Stricter Teacher, More Motivated Students? Comparing the Associations Between Teacher Behaviors and Motivational Beliefs of Western and East Asian Learners - Jiang, Yushan; Lee, Chi-Kin John; Wan, Zhi Hong; Chen, Junjun (Frontiers in Psychology, 2021)
Teacher behaviors are one of the most significant factors influencing student learning. Students from different cultures may have different interpretations of their teachers’ behaviors. This study compared the associations between teacher strictness, teacher feedback and students’ motivational beliefs using data from six Western countries (the United States, the United Kingdom, Finland, Norway, Australia and New Zealand) and six East Asian regions (Japan, Korea, mainland China, Hong Kong, Macau and Taiwan) in the Program for International Student Assessment (PISA) 2015. 89,869 15-year-old students were included in data analysis. The findings indicate that (i) teacher strictness was negatively associated with Western students’ motivation, but positively related to that of East Asian students; (ii) teacher feedback had significant positive associations with the motivational beliefs of both Western and East Asian students; and (iii) there was a positive relationship between teacher strictness and teacher feedback in East Asian context. These results highlight the need to consider cultural factors when interpreting students’ reactions to teacher behaviors.